Validity of Self-Reported Diagnosis of Osteoporosis in Japan Nurses’ Health Study - Kurabayashi, Takumi; Ideno, Yuki; Nagai, Kazue; Maruoka, Naho; Takamatsu, Kiyoshi; Yasui, Toshiyuki; Hayashi, Kunihiko (Clinical epidemiology, 2021)
Although the validity of self-reported osteoporosis is often questioned, validation studies are lacking. This study was performed to investigate how well self-reported diagnoses of osteoporosis agreed with validated clinical information in young and middle-aged women in the Japan Nurses' Health Study (JNHS), a nationwide prospective cohort study of nursing professionals. Data were reviewed for 15,717 subjects from the combined cohorts of the JNHS and a preceding pilot study (Gunma Nurses' Health Study). The subjects' mean age at the baseline (BL) survey was 41.6 ± 8.3 years, and the mean follow-up period was 11.5 ± 4.4 years. Participating nurses were mailed a follow-up questionnaire every 2 years. Respondents who self-reported a positive osteoporosis diagnosis during the study period were sent an additional confirmation questionnaire to corroborate the details. The number (proportion) of women with osteoporosis was 884 (5.6%) [primary osteoporosis, 812 (5.2%); secondary osteoporosis, 72 (0.5%)]. The cumulative incidence of osteoporosis at the age of 40, 50, 60, 70, and 80 years was estimated to be 0.1% (95% confidence interval, 0.1-0.2), 1.1% (0.9-1.3), 7.7% (7.0-8.4), 23.6% (21.6-25.7), and 54.2% (40.2-68.1), respectively. For BL and regular follow-up + expert review versus BL and regular follow-up + confirmation questionnaire + expert review, the positive predictive value (PPV) was 61.3% versus 85.6% and the negative predictive value (NPV) was 98.9% versus 98.2%, respectively. Self-reporting was associated with a high NPV for the incidence of osteoporosis. Although the PPV was slightly lower, additional corroborations by confirmation questionnaire might improve the PPV.